Current views on the role and pathogenesis of osteoarthritis of the knee - Dyndor, Przemysław; Dyndor, Katarzyna; Maciejewski, Ryszard; Jabłoński, Mirosław (Polish Journal of Public Health, 2012)
Osteoarthritis (OA) is the most common condition of the motor system accompanied by chronic pain and disability. It is characterized by articular cartilage degradation, subchondral bone lesions and a local inflammation within the joint. High costs of treatment and great incidence of OA have led to recognizing this condition as a civilization-related disease. In Poland eight million people suffer from OA. In 40% of the cases the disease is located in hip joints and in 25% knee joints. The prevalence increases with age and overweight and obesity create favorable conditions for the development of the disease. People who were obese in their childhood or adolescence are more likely to suffer from OA. The main clinical symptoms include pain, edema, stiffness, limited function and scope of movement and joint malformation. Radiology is the most available diagnostic technique to assess OA. In early diagnostics of articular cartilage pathology the best option is to combine ultrasonography and magnetic resonance imaging. Currently, in order to assess the size and location of defects of articular cartilage doctors perform arthroscopy. The main components of this hypocellular tissue are chondrocytes and amorphous intercellular substance which in turn is composed of cartilage matrix and densely packed collagen fibers. Chondrocytes are typically spherical and hexagonal shaped cells. They account for less than 1% of the volume of mature cartilage and are surrounded by pericellular matrix. They have the ability to produce type II collagen and aggrecans. The most important feature of chondrocytes obtained from OA patients is their hyperreactivity. While the most important factor of self-healing is the interaction between collagen matrix and proteoglycans.Osteoarthritis prevention is prognostically useful.